MAIN PROCESSES IN AXIOLINGUISTICS (Scientific journal of the Fergana State University, 2026)
This article presents a comprehensive analysis of the main processes in the fields of axiology and axioloinguistics – axiology, evaluation, and ranking. The research focuses on the unique role of language in expressing values, examining its semantic and stylistic features as well as identifying contextual changes. Analytical and componential methods are applied in the study, along with interdisciplinary approaches from pragmatics, stylistics, and sociolinguistics to explore the mechanisms of expressing axiological processes.The article provides a detailed analysis of the differences between the evaluation process and axiological terms, their interrelation with the ranking process, and the role of language in expressing evaluative content. The study demonstrates that the processes of evaluation and ranking serve as the primary tools in linguistics for measuring values and determining their hierarchical structure. At the same time, the expression of values through language is shaped in accordance with the cultural, social, and ideological structures of society.This article not only enriches the theory and methodology of linguistics but also contributes to a deeper understanding of the role of language in socio-cultural life. The research findings establish new theoretical approaches and analytical methods for future scientific investigations and highlight the importance of interdisciplinary methods in studying the mechanisms of expressing values through language.